Corredor cultural y peatonal, de la calle 3 del municipio de Rovira- Tolima (2022)
The municipality of Rovira stands out within the department of Tolima, in economic, environmental and sociocultural aspects. On the other hand, the municipality is made up of 82 villages in its rural area and its proximity to major cities and surrounding towns; the urban center of Rovira, becomes an important collection point that welcomes immediate residents and visitors. That is why Rovira, receiving so many people daily, the need for public space arises and it is one of the weaknesses in physical and social aspects, there is not enough public space in the urban area of Rovira, currently it has a deficit of 9 m² of public space per inhabitant, of the 10 m² of optimal indicator needed for public space per inhabitant